1992
DOI: 10.1891/0886-6708.7.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Battered Women’s Early Responses on Later Abuse Patterns

Abstract: Abused women (N = 234) were interviewed using a structured questionnaire to determine whether violence increases during the course of an abusive relationship. Comparisons were made between women with short-term violence and long-term abusive relationships to assess whether strategies used by victims during early incidents affected the duration of the violence. Women out of the relationship were also contrasted with women still in the relationship. The data supported the picture of increasing abuse for 18 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 0 publications
2
20
0
1
Order By: Relevance
“…Their partners attempted to control and isolate the women from family and friends and called them names or insulted them within the first 6 months of their current relationship; this escalated into physical abuse during the second 6 months or third 6 months of the relationship. This is consistent with research that reported the escalation of abuse during the first year of the relationship (Follingstad, Hause, Rutledge, & Polek, 1992;Frisch & MacKenzie, 1991), after which time it leveled off and remained fairly consistent (Follingstad et al, 1992). For a few women (12%) minor physical abuse occurred within the first few months of the relationship but did not escalate to major abusive episodes until 5 or more years into the marriage.…”
Section: Partner Violence: Context Of the Relationshipsupporting
confidence: 89%
See 1 more Smart Citation
“…Their partners attempted to control and isolate the women from family and friends and called them names or insulted them within the first 6 months of their current relationship; this escalated into physical abuse during the second 6 months or third 6 months of the relationship. This is consistent with research that reported the escalation of abuse during the first year of the relationship (Follingstad, Hause, Rutledge, & Polek, 1992;Frisch & MacKenzie, 1991), after which time it leveled off and remained fairly consistent (Follingstad et al, 1992). For a few women (12%) minor physical abuse occurred within the first few months of the relationship but did not escalate to major abusive episodes until 5 or more years into the marriage.…”
Section: Partner Violence: Context Of the Relationshipsupporting
confidence: 89%
“…For most, the escalation of abuse followed a pattern: minor abuse within the first 6-month period of the relationship escalating to major abuse during the second and third 6-month periods. Previous studies have reported similar patterns of escalation (Follingstad et al, 1992;Frisch & MacKenzie, 1991). Early abuse was subtle enough for women not to recognize it as such, and a few even questioned whether minor abuse, such as slapping and pushing, was violence.…”
Section: Resultsmentioning
confidence: 98%
“…Hence, battered women do not stay in abusive relationships because they want to be abused, but because of their positive expectations of the relationship's future (Ahmad et al 2009). Indeed, research has found that if the batterer shows no remorse and does not treat the woman better during the honeymoon phase, the latter tends to leave (Follingstad et al 1992). We propose that similar compensatory behaviors are also present in mentoring relationships.…”
Section: Cycle Of Violence Theory: 'Rainbow After the Storm'mentioning
confidence: 74%
“…Indeed, research has found that if the batterer shows no remorse and does not treat the woman better during the honeymoon phase, the latter tends to leave (Follingstad et al. ). We propose that similar compensatory behaviors are also present in mentoring relationships.…”
Section: Cycle Of Violence Theory: ‘Rainbow After the Storm’mentioning
confidence: 99%
“…Reports provide several explanations for abused women's utilization of health care. For example, abused women may not utilize health care until the severity of the abuse escalates (Follingstad, Hause, Rutledge, & Polek, 1992;Leserman, Li, Drossman, & Hu, 1998). Other studies describe barriers to adequate utilization of health care for abuse related injuries including cultural constructs that discourage disclosing the abuse (Tjaden & Thoennes, 2000b) or because the abused woman fears that her children will be taken away from her (Loue, 2001;Zink & Jacobson, 2003).…”
Section: Implications and Clinical Applicationsmentioning
confidence: 99%